Characteristics of plasma disruption mitigation achieved by MGI and SPI on EAST - S.B. Zhao; J.S. Yuan; H.D. Zhuang; G.Z. Zuo; L. Li; T. Tang; L. Zeng; Y.M. Duan; T.H. Shi; S.T. Mao; D.L. Chen; M. Huang; et al. (Nuclear Fusion)
This study systematically compares the influence of shattered pellet injection (SPI) and massive gas injection (MGI) on plasma disruption mitigation within the Experimental Advanced Superconducting Tokamak. The results reveal that SPI demonstrates significant advantages over MGI in plasma disruption mitigation, as it predominantly deposits impurities within the plasma core. This leads to more rapid emission of thermal radiation and a significantly shorter total disruption duration compared to MGI. Conversely, MGI primarily deposits impurities at the plasma edge, and its impurity penetration duration is longer compared to that of SPI. During the current quench phase, MGI displays an evident radiation tail extending from the plasma core to its edge, accompanied by a second current spike. These phenomena are primarily attributed to cold vertical displacement events, which cause the plasma to directly contact the first wall, thereby generating halo currents and emitting hard x-rays. Furthermore, both SPI and MGI exhibit clear magnetohydrodynamic (MHD) mode switching, wherein the inherent n = 1 and n = 2 modes transition to a new n = 1 mode. This new mode features a reversed rotation direction and is accompanied by a burst of soft x-rays from the plasma core. This observation suggests that the observed MHD mode switching is driven by impurity‒plasma interactions rather than the impurity injection method. Future research endeavors must focus on high-resolution diagnostics and further experimentation to better understand the impacts of impurities on MHD modes. Overall, this study provides crucial data support for improving plasma disruption mitigation strategies for ITER and other future fusion reactors.